A standard component for photovoltaic module electrical performance test - TANG YUNHE; ZHANG YUJUN; HUANG QIANG (2017)
The utility model relates to a standard component for photovoltaic module electrical performance test. Above -mentioned a standard component for photovoltaic module electrical performance test is including the positive glass, transparent EVA encapsulated layer, solar cell layer, white EVA encapsulated layer and the back glass that stack gradually, positive glass's thickness is 2.5mm~4mm, back glass's thickness is 2mm~3.2mm. Among the above -mentioned a standard component for photovoltaic module electrical performance test, adopt positive glass and back glass to combine, just positive glass's thickness is 2.5mm~4mm, and back glass's thickness is 2mm~3.2mm, has effectively improved whole a standard component for photovoltaic module electrical performance test's bending resistance and has rolled over and shock resistance to the whole anti latent ability of splitting of above -mentioned a standard component for photovoltaic module electrical performance test has been increased. In addition, be white EVA encapsula